Methods to promote germination of dormant Setaria viridis seeds. - Jose Sebastian (Public Library of Science (PLoS), 2014)
Setaria viridis has recently emerged as a promising genetic model system to study diverse aspects of monocot biology. While the post-germination life cycle of S. viridis is approximately 8 weeks long, the prolonged dormancy of freshly harvested seeds can more than double the total time required between successive generations. Here we describe methods that promote seed germination in S. viridis. Our results demonstrate that treating S. viridis seeds with liquid smoke or a GA3 and KNO3 solution improves germination rates to 90% or higher even in seeds that are 6 days post-harvest with similar results obtained whether seeds are planted in soil or on gel-based media. Importantly, we show that these treatments have no significant effect on the growth of the adult plant. We have tested these treatments on diverse S. viridis accessions and show variation in their response. The methods described here will help advance research using this model grass species by increasing the pace at which successive generations of plants can be analyzed.